Confronting psychological and social pressures and their relationship to psychological adjustment for the wives of the martyrs - Adawi, Lubna Mohammed AbdelRahman (Journal of Educational and Psychological Sciences, 2020)
This study aimed to clarify the level of psychological and social pressures and the level of psychological adaptation among the wives of the martyrs, through relying on the study tool (the questionnaire), which consisted of (30) paragraphs the researcher used to study the level of the study variables and their relationship with each other, and the researcher collected the opinions of the study sample Which consisted of (200) wife of a martyr, and the results showed an increase in the level of psychological and social pressures faced by the wives of the martyrs in addition to the high level of psychological adaptation to them, the results also showed a statistically significant correlation between levels of facing psychological and social pressure The psychological impact of martyrs ’wives in Palestine, and the absence of statistically significant differences between levels of coping with psychological and social pressures among martyrs’ wives in Palestine due to the age variable, marital status, place of residence, educational attainment, number of years of husband’s martyrdom, work, number of children, in addition to The absence of statistically significant differences between the levels of psychological adaptation of the wives of the martyrs in Palestine due to the variable of age, marital status, place of residence, educational attainment, the number of years of the husband's martyrdom, work, the number of children, and the researcher recommended the need to work on providing psychological and social support for the wives of the martyrs By activating the role of civil and governmental organizations which reduces the psychological and social pressures facing them, and supporting the wives of the martyrs by providing financial and psychological support to them through working to find jobs and businesses that contribute to changing their conditions and enabling them to re-engage in society, which helps them to increase the level of Their psychological adaptation, and the organization of feminist workshops with the wives of the martyrs to talk about their different experiences and communicate to benefit from each other's experiences, which increases their ability to face the psychological and social pressures surrounding them.
Keywords: psychological pressure; social pressure; psychological adjustment; the wives of martyrs